Implikasi Hukum Atas Penggunaan Teknologi dalam Pelayanan Kesehatan Telemedicine - Manurung, Hanafi; Sianturi, Handri Michael; Isnainul, Ok.; Sahbudi (Cattleya Darmaya Fortuna, 2024)
Telemedicine is the use of information and communication technology to provide remote healthcare services. This encompasses online doctor consultations, diagnosis, treatment, and patient health monitoring without the need for physical meetings. Telemedicine utilizes various platforms, such as mobile applications and video conferences, to connect patients with healthcare providers. With the increasing demand for fast and efficient healthcare access, especially in remote areas, telemedicine has become an increasingly popular solution worldwide, including in Indonesia. The purpose of this study is to identify and analyze the legal implications arising from the use of telemedicine, assess the protection of patient data, and examine the legal responsibilities of healthcare providers. The methodology employed in this research is qualitative descriptive, where data is collected through document studies and literature reviews to obtain a comprehensive overview of the legal issues related to telemedicine. The discussion reveals that there is uncertainty in regulations that can create confusion for both service providers and patients. Additionally, the protection of personal data is a critical issue, given the risks of medical information breaches. The legal responsibilities of service providers also need to be clarified to avoid potential litigation arising from diagnostic or treatment errors. On the other hand, telemedicine has the potential to enhance access and efficiency in healthcare services, especially in remote areas. In conclusion, this study emphasizes the need for a clear legal framework to protect all parties involved in telemedicine practices. With collaboration between the government, healthcare providers, and the community, it is hoped that telemedicine can develop positively, providing maximum benefits to the healthcare system in Indonesia.